ULTRASONOGRAPHY IN THE INVESTIGATION OF TEMPOROMANDIBULAR JOINTS: PROBLEMS AND PROSPECTS - D.V. Shtybel; R.V. Kulinchenko; A.V. Dvornyk (Український стоматологічний альманах)
Ultrasonography (USG) can be considered as a useful method for rapid screening of patients with suspected temporomandibular disorders (TMDs). It is necessary to select USG parameters of the temporomandibular joint (TMJ) and the masticatory muscles (MM) with unambiguous interpretation and to standardize them (determine the norm and reference points of measurement).